La crisis sanitaria y su incidencia en la producción audiovisual - Maruri Flores, Hillary Lesli (2022)
The present estudy analyzes a theme about audiovisual production, we will try to emphasize how the production companies and television channels developed because of the Covid 19 pandemic. In this sense, the stated objective sought to analyze the effectiveness of the strategies of innovation implemented by the audiovisual producers of Record TV Producciones and Canal de la Católica. Faced with this problem, many changes have been observed to be able to get ahead with their programs and not opt for the option of closing them, to achieve this, they had to adapt to the new methods that technology offers us and, in this way, continue generating audiovisual content for their programs. viewers.......